If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + -9) = 42 Reorder the terms: -4(-9 + x) = 42 (-9 * -4 + x * -4) = 42 (36 + -4x) = 42 Solving 36 + -4x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -4x = 42 + -36 Combine like terms: 36 + -36 = 0 0 + -4x = 42 + -36 -4x = 42 + -36 Combine like terms: 42 + -36 = 6 -4x = 6 Divide each side by '-4'. x = -1.5 Simplifying x = -1.5
| 5x-12+7x+4= | | 64m^2+7=16 | | 2x+90=85 | | -3+4=-5-9 | | 2(x+6)=4(3x) | | 4x-8=(x-4) | | 36+N=63 | | 3a+b-45=2a+4b+465.23+a+103b | | 13-x/7=-1 | | -1/5a+7=(-11) | | (x+2x+5)-10=22 | | 5/8x24 | | a/b-45=2a+4b+465.23+a+103b | | 1/4(8x-16)=6x+2 | | ab-45=2a+4b+465.23+a+103b | | -15-(-8)+7= | | ab-45=2a+4b+465.23+a+103ab | | -1-6k=-7k-19 | | 2+25p^2=66 | | 10a+15a=75 | | 2x+6=-6x-34 | | -7s+4=-7-8s+4 | | 6-7i/6+7i | | 60=-5x+10 | | 8v+35=7(6v+5) | | (1/2x)=32 | | 2g-14=g | | 4(y+2)=15 | | ab-45=2a+4b+465.23+a | | 156/180=x/120 | | (1-2x)=32 | | 13x-68=-7x+12 |